Peningkatan Literasi Keuangan Melalui Kreasi Celengan Hias Di Sekolah Dasar - Qanitah Masykuroh; Ridhanti Sulistyaningrum; Isna Febi Nuraini; Diah Nur Aisyah (UNIB Press, 2023)
Preliminary observation shows the low interest of children to do saving at school, which is indicated by the small number of students who save regularly every week. This, together with the lack of children's understanding of saving become the basis for the community service activity. This community service activity aims to educate school-age children to provide literacy about the benefits of saving, invite children to learn to set aside some of their money for savings, and increase children's creativity by decorating piggy banks. Activities were carried out for grade 5 and 6 students at SD Negeri Getan 02, Bulu, Sukoharjo. The results of this service activity show that elementary-age students can be given an understanding of financial literacy, especially saving, in a fun way where students are enthusiastic in listening to explanation, and have question and answer session. Furthermore, the activity of decorating piggy banks by drawing, and sticking both using paper and seeds can arouse student motivation related to increasing interest in saving which is part of an effort to build financial literacy from an early age.